CHARACTERIZATION AND CELULAR PROLIFERATION OF OVARIAN STRUCTURES OF EWES BY THE TECHNIQUE OF AGNOR: OVARIAN MORFOMETRY AND CORRELATIONS - Chacur, M. G. M.; Arrebola, T. A. H.; Ibrahim, D. B.; Sanches, O. C.; Gabriel Filho, L. R. A.; Cremasco, C. P.; Putti, F. F. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The AgNOR staining technique for nucleolar organizer regions (NORs) is characterized by marking proteins related to ribossomal ribonucleic acid evaluating celular proliferation. The objective was to study the ovarian morphometry and the value of AgNOR thecnique application to evaluate the proliferation of healthy cels from ovarian structures in crossbred ewe. 102 pairs of ovaries were collected and from the largest follicle of each ovary was measured its diameter. From the largest corpus luteum (CL) was measured the diameter and width, classifying the CL in: included, protruberant, massive and cavity, followed by AgNOR staining. The significance level was 5%. It had difference (p<0.05) for the diameter of the largest follicle between right (RO): 4.2±2,3mm and left (LO): 3.6±2,2mm sides. There was a correlation (p<0.01) between the NORs of internal theca (IT) and external theca (ET): RO (0.46) and LO (0.61); NORs of granulosa and IT: RO (0.54) and LO (0.59); and NORs of granulosa and ET: RO (0.34) and LO (0.38). Was conclude that the NORs quantification was appropriate to study the determination of the potential for ovarian structures proliferation, which was similar for right and left sides.